1981
DOI: 10.1136/hrt.46.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of electrocardiographic findings in angina at rest. Therapeutic implications.

Abstract: SUMMARYNinety-five patients with angina at rest were observed in the coronary care unit. Eighty-one per cent presented concomitantly or had previously presented some other manifestations of coronary artery disease. These patients were divided into two subgroups. In subgroup 1 (40 patients), episodes of non-exertional angina were associated with a pattern of hyperacute subepicardial injury and, frequently, with ventricular arrhythmias. In subgroup 2 (55 patients), the episodes of angina at rest were attended by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…T-wave inversion has been reported in humans. 30,31 One case report, consistent with our observations, showed T-wave inversion associated with amiodarone toxicity in an attempt at suicide. 30 However, there are no reports in dogs about T-wave inversion.…”
Section: Discussionsupporting
confidence: 83%
“…T-wave inversion has been reported in humans. 30,31 One case report, consistent with our observations, showed T-wave inversion associated with amiodarone toxicity in an attempt at suicide. 30 However, there are no reports in dogs about T-wave inversion.…”
Section: Discussionsupporting
confidence: 83%
“…(Circulation 1989;79:154-166) It is currently believed that the pathophysiology of unstable angina is a primary reduction in coronary blood flow. [1][2][3][4][5][6] In particular, there is a growing body of evidence indicating that in most patients, unstable angina is the consequence of sudden restorations of flow. These alterations in coronary blood flow have been referred to as cyclic flow variations and are caused by transient formation of platelet thrombi at the site of the coronary stenosis and endothelial injury.14-17Subsequent studies from our laboratory have demonstrated that serotonin (5HT) and thromboxane A2 (TXA2) released from activated platelets are two important mediators of cyclic flow variations in this canine model15,17"8 and that the tissue concentration of 5HT and TXA2 is markedly elevated in the coronary artery at the site of the stenosis.…”
mentioning
confidence: 99%